2005
DOI: 10.1074/mcp.m500044-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Differentiation-related Gene 1 Expression by Cell Cycle Blocker Mimosine, Revealed by Proteomic Analysis

Abstract: L-Mimosine, a plant amino acid, can reversibly block mammalian cells at late G 1 phase and has been found to affect translation of mRNAs of the cyclin-dependent kinase inhibitor p27, eIF3a (eIF3 p170), and ribonucleotide reductase M2. The effect of mimosine on the expression of these genes may be essential for the G 1 phase arrest. To determine additional genes that may be early respondents to the mimosine treatment, we performed two-dimensional gel electrophoretic analysis of [35 S]methionine-labeled cell lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Furthermore, there is work demonstrating that Fe-depletion by DFO can up-regulate ATF3. 198 This latter observation appears somewhat paradoxical, as the observed up-regulation of Ndrg-1 after Fe-depletion 102,110 would be expected to downregulate ATF3 levels.…”
Section: The Molecular Targets Of Iron Chelators and Their Effects Onmentioning
confidence: 59%
See 3 more Smart Citations
“…Furthermore, there is work demonstrating that Fe-depletion by DFO can up-regulate ATF3. 198 This latter observation appears somewhat paradoxical, as the observed up-regulation of Ndrg-1 after Fe-depletion 102,110 would be expected to downregulate ATF3 levels.…”
Section: The Molecular Targets Of Iron Chelators and Their Effects Onmentioning
confidence: 59%
“…102 The effect of Fe-deprivation on up-regulated Ndrg-1 levels in HeLa cells was confirmed by others in later studies using the chelator, mimosine. 110 Both HIF-1a-dependent and -independent mechanisms were found to be responsible for the up-regulation of Ndrg-1 following Fe-depletion. 102 The addition of Fe salts to cells after Fe chelation was found to reverse Ndrg-1 upregulation, confirming that Fe-depletion increased Ndrg-1 expression.…”
Section: The Molecular Targets Of Iron Chelators and Their Effects Onmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence implicating other tumor suppressors, such as, the retinoblastoma gene (Goodrich, 2006), p53 (Spike and Wahl, 2011), DCC gene (Zhao, 2012), and Differentiation-Related-Gene-1 (Drg-1) (Dong et al, 2005) in cellular differentiation. Results of the molecular control of changes in the normal developmental program in myeloid leukaemia have shown that genetic abnormalities which give rise to malignancy can be bypassed, and their effects nullified, by inducing differentiation, which stops cells from multiplying (Lai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%